β‐Glucuronidase‐Expressing Lactobacillus reuteri Triggers Irinotecan Enterotoxicity Through Depleting the Regenerative Epithelial Stem/Progenitor Pool - Bei Yue; Ruiyang Gao; Ling Zhao; Donghui Liu; Cheng Lv; Ziyi Wang; Fangbin Ai; Beibei Zhang; Zhilun Yu; Xiaolong Geng; Hao Wang; Kang Wang; et al. (Advanced Science)
Abstract Irinotecan (CPT11)‐induced diarrhea affects 80–90% of cancer patients due to β‐glucuronidase (GUS) converting 7‐ethyl‐10‐hydroxycamptothecin glucuronide (SN38G) to 7‐ethyl‐10‐hydroxycamptothecin (SN38). It remains unclear whether SN38 impacts the homeostasis between gut microbiota and mucosal stem cell niche. This study explores the crosstalk between gut microbiota and intestinal stem cells (ISCs) in intestinal mucositis triggered by CPT11 chemotherapy. CPT11‐treated mice exhibited significant colon shortening, inflammatory infiltration, intestinal barrier dysfunction, and ISC impairment, which correlated with gut dysbiosis, enrichment of GUS‐expressing bacteria, and intraluminal SN38 accumulation. In contrast, antidiarrheal (Xianglian pill) treatment alleviated SN38‐induced enterotoxicity and reduced GUS‐expressing bacterial populations. Microbiome profiling of clinical patients and mucositis mice revealed a strong correlation between CPT11/SN38 enterotoxicity and GUS‐expressing bacteria, particularly Lactobacillus reuteri. PLS‐PM modeling further linked L. reuteri to impaired epithelial regeneration, which is validated using a 3D intestinal organoid model. L. reuteri hindered ISC differentiation into secretory lineages within the organoids. Furthermore, L. reuteri colonization in mice exacerbated mucositis and disrupted epithelial differentiation, while its elimination ameliorated colitis symptoms and preserved crypt cell stemness. These findings suggest that selectively targeting GUS‐expressing bacteria, particularly L. reuteri, to protect the regenerative epithelial stem/progenitor pool may serve as an effective strategy for mitigating CPT11‐induced enterotoxicity.